Sonographic findings of the synovial fluid - A. Farina; E. Filippucci; W. Grassi (PAGEPress Publications, 2002)
Objective: The aim of this pictorial essay was to evaluate the sonographic features of synovial fluid in patients with arthritis. Methods: Sixty-nine patients with active synovitis (rheumatoid arthritis, psoriatic arthritis, osteoarthritis, septic arthritis, crystal arthropathies, post-traumatic arthritis) were studied. Sonographic evaluation was performed with a AU-5 Harmonic, Esaote Biomedica (Genoa, Italy) equipped with a 10-14 MHz broadband linear transducer and a Diasus Dynamic Imaging Ltd.(Livingston, Scotland UK) equipped with a 8-16 MHz broadband linear transducer. Results: Six main different sonographic patterns were detected: 1) Anechoic: increased amount of homogeneous anechoic synovial fluid (exudative synovitis). 2) Cloudy: ecogenic structures (proteinaceous material). 3) Mixed: anechoic synovial fluid and proteinaceus material. 4) "Snow-storm" aspect: multiple mildly and heterogeneous echoic spots (9 out of 10 patients with acute gouty synovitis). 5) Dotted: multiple sparkling hyperechoic dots without posterior acoustic shadow (10 out of 12 patient with chondrocalcinosis). 6) Granular: irregular turbid aspect of the synovial fluid. It was present in 3 patient with septic arthritis. Conclusions: The results of this study indicate that high resolution ultrasonography is able to detect different features of synovial fluid. Further studies are needed to assess both sensitivity and specificity of ultrasonography in "in vivo" synovial fluid examination.